2000
DOI: 10.1034/j.1600-048x.2000.310304.x
|View full text |Cite
|
Sign up to set email alerts
|

Body size and determinants of laying date variation in the Snow Petrel Pagodroma nivea

Abstract: We studied several determinants of laying date variation and the relationship between laying date and reproductive success in the Snow Petrel Pagodroma nivea. The effects of female body size and condition, year, individual laying period, colony size, mate fidelity, previous reproductive success, and duration of the pre‐laying exodus on laying date, were investigated during a 3‐year study. The average laying date was 4 December. The laying period was compressed into 10–16 days and was very constant from year to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…The laying period ranges from late November to mid‐December. Within one breeding season, egg‐laying dates differ between individuals over a period of 2 weeks (Barbraud, Lormee & LeNeve 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The laying period ranges from late November to mid‐December. Within one breeding season, egg‐laying dates differ between individuals over a period of 2 weeks (Barbraud, Lormee & LeNeve 2000).…”
Section: Methodsmentioning
confidence: 99%
“…), fledging is all but assured. Thus, hatching success is probably the most critical component of reproductive success for storm-petrel parents, especially given the energetic demands of incubation in seabirds (Ricklefs et al 1986;Chastel et al 1995a;Barbraud and Chastel 1999;Barbraud et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in atmospheric and oceanographic conditions have great effects on seabird diet ) and body condition (Chastel et al 1995a,b;Barbraud et al 2000). Such uncertainty results in high annual variability in seabird reproductive success and survival (e.g., Chastel et al 1993;Erikstad et al 1998;Sydeman et al 2001;Croxall et al 2002).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most challenging areas in evolutionary biology and ecology has been to determine the relationship between adult body size and fitness. Across a range of vertebrate and invertebrate taxa, numerous empirical studies have reported that body size is correlated with life‐history and demographic traits such as mating efficiency, dispersal capability, and, most importantly, lifetime reproductive success (Berrigan, 1991; Blackburn, 1991; Visser, 1994; Luiselli et al ., 1996; Barbraud et al ., 2000; Rasa et al ., 2000; Sokolovska et al ., 2000; Bezemer & Mills, 2003; Bochdanovits & De Jong, 2003; Jervis et al ., 2003; Skow & Jakob, 2003; Wissinger et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%